Evaluasi Tata Ruang dan Pencahayaan pada Rumah Instan Sederhana Sehat (RISHA) di Kampung Deret Petogogan Kebayoran Baru Jakarta Selatan - Sulindra, Muhammad Rizky; Rajiman; Susanti, Junita (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
Simple Healthy Instant Homes (RISHA) was developed as a fast and affordable housing solution to reduce slum settlements and improve housing quality. However, optimal spatial planning and natural lighting are still needed to meet comfort and health standards. This research evaluates the suitability of spatial planning and natural lighting in RISHA housing in Kampung Deret Petogogan, focusing on type 18 and type 36 houses. The methods used include primary and secondary data collection and analysis based on the Housing and Settlement Development Guide and the Healthy Home Module. Evaluation of natural lighting using Dialux Evo 12.1 refers to SNI 03-2396-2001. The research results show that spatial planning suitability reaches 50% in type 18 houses and 53% in type 36 houses, classified as "quite suitable." The distribution of natural light only meets the standard of 50% in type 18 and 40% in type 36, with the multipurpose room and bathroom being the most affected. Improvements are needed in RISHA design to improve occupant comfort and health, such as optimizing openings and transparent materials to increase natural lighting. Further research is recommended to develop more adaptive design strategies for environmental conditions.